Resistência e prática pedagógica operária: o movimento dos operários da Fiat / Diesel e a formação da Associação Cultural de Apoio Mútuo (ACAM) - Moraes, Maria Stela Marcondes de (1984)
In 1972, Fiat, the Italian enterprise, bought the plant of 'Fábrica Nacional de Motores' (FNM), in Xerém, Rio de Janeiro. This fact has determined the insertion of the Brazilian branch into the Fiat internationa1 scheme of production. It has also provoqued important changes in the labour processes so far adopted by the Brazilian factory. Modern management techniques, complemented by the action of advanced techology have caused here the same effects as elsewhere: unemployment and the reduction of the workers' intelectual potentialities. Thus, the possibilities of labour control over the process of production or even over the very labour power of resistance have been extremely reduced. The generalization of these conditions has caused, among other strikes in Brazil, the four movements of the Fiat workers (1978, 1979, 1980, 1981). Masqued by the apparent aspect of these strikes (the immediate economical requests) is the iressential element: the disruption of oppressive labour relations. This can be seen in the organization of collective forms of catering, important element that allow the interruption of competition, hierachy and all kinds of divisions among the workers. Having been dismissed because of their active participation in the strikes, about so workers founded an organism called 'Associação Cultural de Apoio Mútuo' (Acam), where they intended to recreate the conditions for collective organization. From the beginning its difficulties were mainly due to the basic contradictions of the oppressed: forces that simultaneously atract the workers to submission, on the one hand, and to self-government and autonomy, on the other hand. Immediately after the strikes the workers have gone back to the original oppressive relations inside the industrial production processo Three years later Acam closed down having been unable to reach its aims. All this prove the necessity of more lasting and generalized forms of maintenance of the associating relationships create during the strike periods.